A new nanohybrid for electrocatalytic biodiesel production from waste Amalfi coast lemon seed oil. (1st May 2020) - Sarno, Maria; Ponticorvo, Eleonora
Highlights: Biodiesel from waste Amalfi cost lemon seeds oil. No co-solvent, no additional active phases, low voltage electrocatalytic conversion. PtIrRu nanoalloy modified electrode. High activity and stability for a sustainable conversion. Biodiesel agreement with the European Standard. Abstract: A novel electrocatalytic simple method, based on a Pt, Ir and Ru trimetallic nanoalloy (PtIrRu), was explored for the biodiesel production from Amalfi coast waste lemon seeds oil. The experiments were performed in a methanolic reaction mixture, in the absence of toxic co-solvents and active dissolved species, and operating at a moderate voltage. The transesterification reaction occurred with a low amount of nanocatalyst in a two-phase reaction mixture, where an emulsion of oil in the alcohol phase is formed under stirring. A systematic study, looking for combinations ensuring high biodiesel yields, was performed by varying the process parameters. The effects of the voltage, temperature, NaCl content, methanol/oil ratio, reaction time and water content on the methyl esters yield were explored and the products were analyzed. Although temperature does not significantly affect conversion, NaCl content and time were found crucial. Lemon seed oil conversion reached a value of 98.2% after 2 h at 15 V, 0.3 wt% of NaCl and 20 °C, methanol/oil ratio 10:1, water content 2 wt%. Although a methyl esters yield reduction was observed in the presence of water, yields of 80% and 49.2% were still measured at 2 wt% and 4 wt% of water, respectively. The characteristics of the biodiesel produced were in agreement with the EN14214. The results of this paper constitute a proof of concept of the valorization in biodiesel of all lemon seed oils, also considering the large global scale citrus fruit consumption and processing, e.g. to produce fruit juices.